2022
DOI: 10.3390/ijms23105648
|View full text |Cite
|
Sign up to set email alerts
|

H2S in Horticultural Plants: Endogenous Detection by an Electrochemical Sensor, Emission by a Gas Detector, and Its Correlation with L-Cysteine Desulfhydrase (LCD) Activity

Abstract: H2S has acquired great attention in plant research because it has signaling functions under physiological and stress conditions. However, the direct detection of endogenous H2S and its potential emission is still a challenge in higher plants. In order to achieve a comparative analysis of the content of H2S among different plants with agronomical and nutritional interest including pepper fruits, broccoli, ginger, and different members of the genus Allium such as garlic, leek, Welsh and purple onion, the endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Table 1 shows the identified proteins that can generate H 2 S from the two cysteines (Cys) isomers, either L-cysteine (L-Cys) or D-Cys. Thus, we focus on the cytosolic LCD and the mitochondrial DCD that are considered the main sources of H 2 S in higher plants (Mei et al, 2019 ; Muñoz-Vargas et al, 2022 ; Scuffi et al, 2014 ; Yamasaki et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the identified proteins that can generate H 2 S from the two cysteines (Cys) isomers, either L-cysteine (L-Cys) or D-Cys. Thus, we focus on the cytosolic LCD and the mitochondrial DCD that are considered the main sources of H 2 S in higher plants (Mei et al, 2019 ; Muñoz-Vargas et al, 2022 ; Scuffi et al, 2014 ; Yamasaki et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The LCD is considered the main source of H 2 S and catalyzes the following reaction: L-cysteine + H 2 O → pyruvate + NH 4 + + H 2 S + H + , requiring pyridoxal 5′-phosphate (PLP) as a cofactor (Kurmanbayeva et al, 2022 ; Muñoz-Vargas et al, 2022 ). LCD participates in diverse physiological processes such as root development (Mei et al, 2019 ), stomatal closure (Ma et al, 2021 ; Scuffi et al, 2014 ; Shen et al, 2020 ), leaf senescence (Hu et al, 2021 ), fruit ripening (Hu et al, 2020 ; Muñoz-Vargas et al, 2018 ), but also in the mechanism of response to diverse environmental stresses (Kaya, 2020 ; Kharbech et al, 2022 ; Sun et al, 2022 ; Wang et al, 2022 ; Wang et al, 2023 ; Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the results of PCA levels indicated stronger positive associations between NO- or AA-primed stressed plants and the content of this signaling molecule than those observed under stress conditions. Numerous studies have confirmed the functional parallelism of NO and H 2 S in mediating multiple physiological pathways under harsh conditions [ 106 ]. Many investigations have deduced the involvement of H 2 S in NO-mediated salinity or heavy metal stresses of many plants [ 107 , 108 , 109 ], which supports the role of NO, or possibly AA, in the mitigation of salinity and/or Li stress through the upregulation of endogenous H 2 S.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between NO and H 2 S may lead to modifications in protein function and signaling pathways, which are essential for the plant’s adaptation to water scarcity. The role of L-DES in mediating the production of H 2 S from l -cysteine has been recognized as a significant factor in plant stress physiology (Shen et al 2019 ; Muñoz-Vargas et al 2022 ). Furthermore, the interplay between NO and H 2 S has been shown to involve various post-translational modifications, including S-nitrosylation and persulfidation, which affect protein activity and cellular signaling under stress conditions (Aroca et al 2018 ; Singh et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%